Effects of the Topography of Sumatra on Tropical Cyclone Formation over the Indian Ocean (MAUSAM, 2026)
One-quarter of the world’s tropical cyclones (TCs) occur in the Indian Ocean (IO) basin.The mechanisms for TC initiation in the IO are varied, but one recently discovered process involves the flow around the steep topography of Sumatra.  When the low-level flow impinges on Sumatra, it is blocked and the flow splits under typical environmental stratification.  As a result, wake vortices commonly develop at northern and southern island tips of the island. For the case of easterly flow, these circulationssubsequently move downstream over the IO.  The wake vortices emanating from the island tips are counter-rotating, but since Sumatra straddles the equator, the circulations are cyclonic in both hemispheres and thus have the potential for TC development. Using data from2.5yearsof observations from DYNAMO and YOTC, it is found that approximately 25% of the TCsthat occurred overIO basin during that periodwere initiated by Sumatra-induced wake vortices.Additional analysis of vortex statistics for the period 2008-17 has found that vortex counts are highest near Madden-Julian Oscillation (MJO) phase 1 when low-level easterlies are strongest across southern Sumatra. A secondary peak in vortex formation occurs during MJO phase 4 when low-level westerlies exist near the equator west of Sumatra. The latter finding suggests that MJO-related, low-level westerly surges on the equator impinging on Sumatracontribute to an increase in wake vortex development.  Numerical simulations have shown that circulations farther upstream such aswestern Pacific remnant TCs and the Borneo vortex can influence the development of Sumatra wake vortices and their growth into TCs over the IO.